The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12010-008-8291-3
|View full text |Cite
|
Sign up to set email alerts
|

Some Methods for Human Liquid and Solid Waste Utilization in Bioregenerative Life-Support Systems

Abstract: Bioregenerative life-support systems (BLSS) are studied for developing the technology for a future biological life-support system for long-term manned space missions. Ways to utilize human liquid and solid wastes to increase the closure degree of BLSS were investigated. First, urine and faeces underwent oxidation by Kudenko's physicochemical method. The products were then used for root nutrition of wheat grown by the soil-like substrate culture method. Two means of eliminating sodium chloride, introduced into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The method of oxidation of human exometabolites was published earlier [2]. As a result such oxidation, a gas mixture is released from the reactor and a mineral solution is formed in the reactor, which, after a special pretreatment, can be used as a fertilizer for growing plants [4]. The gas mix ture released at the stage of electrochemical oxidation was collected in gasholders.…”
Section: Methodsmentioning
confidence: 99%
“…The method of oxidation of human exometabolites was published earlier [2]. As a result such oxidation, a gas mixture is released from the reactor and a mineral solution is formed in the reactor, which, after a special pretreatment, can be used as a fertilizer for growing plants [4]. The gas mix ture released at the stage of electrochemical oxidation was collected in gasholders.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the SLS appeared to be the basic runoff for Na that might result in its gradual salinization. The solution ways of that problem were investigated in a separate paper (Ushakova et al, 2008). Measurements of concentrations of water-soluble nitrogen in irrigation solutions in the course of plant growth in Treatments 1 and 2 showed that during the first 4 weeks the Table 1 Counts of microorganisms in 1 ml of suspension.…”
Section: The Effects Of Human Wastes Oxidized To Different Degrees Onmentioning
confidence: 99%
“…This idea is proposed by A. Tikhomirov in cooperation with J.-B. Gros [9,[33][34][35] and developed by Liu et al [20]. Basic characteristics of SLS is a similarity to organogenic fertile soils.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of composting lunar fines with waste products from a manned base was proposed by Walkinshaw and Galliano [37]. Formation of a protosoil by microorganisms, composting crop residues, for purposively growing plants is being studied [9,[33][34][35]. Nowadays it seems to be practical to integrate in situ terraforming and waste recycling systems with ISRU to accommodate PMLB and to reduce the demand for energy, transfer mass and cost of future exploration [17,18].…”
Section: Introductionmentioning
confidence: 99%